2017
DOI: 10.1007/s10461-017-1860-0
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use, HIV Treatment Adherence, and Sexual Risk Among People with a History of Injecting Drug Use in Vietnam

Abstract: Alcohol use can limit the effectiveness of antiretroviral therapy (ART) for people living with HIV (PLH) who have a history of injecting drug use. This study described the patterns of alcohol use among PLH with a history of injecting drug use in Vietnam and examined the relationships between alcohol use, adherence to ART, and sexual risks. We utilized cross-sectional data of 109 PLH on ART collected from a randomized controlled intervention trial in Vietnam. Approximately 30 and 46% of the participants were fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
(52 reference statements)
1
4
0
1
Order By: Relevance
“…Of our PLH participants, nearly all (95.4%) were on ART and received HIV treatment separately at the same clinic. These findings support research documenting the co-occurrence of substance use disorders and HIV in Vietnam [ 25 ].…”
Section: Discussionsupporting
confidence: 88%
“…Of our PLH participants, nearly all (95.4%) were on ART and received HIV treatment separately at the same clinic. These findings support research documenting the co-occurrence of substance use disorders and HIV in Vietnam [ 25 ].…”
Section: Discussionsupporting
confidence: 88%
“… 2 In low-income and middle-income countries, hazardous alcohol use among PWH is common, with 20% to 46% of PWH reporting hazardous alcohol use. 3 , 4 , 5 , 6 , 7 , 8 , 9 Alcohol use has been associated with decreased adherence to antiretroviral therapy (ART) 10 , 11 , 12 and decreased viral suppression. 13 Alcohol use is also associated with elevated sexual and injection risk behaviors that increase the likelihood of HIV transmission.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Alcohol use is also associated with elevated sexual and injection risk behaviors that increase the likelihood of HIV transmission. 7 , 14 , 15 , 16 Despite the known adverse health consequences of alcohol use, there is a lack of evidence-based interventions for PWH, 17 , 18 , 19 , 20 , 21 and hazardous and heavy alcohol consumption are frequently not addressed in HIV health care settings.…”
Section: Introductionmentioning
confidence: 99%
“…Hazardous alcohol use, defined as more than 14 drinks per week for men and more than 7 drinks per week for women [ 10 ], impacts persons with HIV (PWH) disproportionately. Previously published research from northern Vietnam identified the need for alcohol treatment services and identified the barriers to medication adherence among PWH with hazardous alcohol use [ 8 , 11 13 ]. In 2015 only half of all PWH in Vietnam were receiving antiretroviral therapy (ART) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%